Utilization of Quizizz Educational Game Media to Increase Learning Interest and Achievement - Rina Yuliana Pratama (Indonesian Journal Of Educational Research and Review, 2021)
When explaining the material, the teacher only uses blackboard learning media and is monotonous. This has an impact on student learning outcomes are low. This study aims to analyze the effectiveness of the Quizizz Game learning media in increasing enthusiasm and learning outcomes. This type of research is classroom action research. The research subjects were fourth-grade students with 23 students. The data in this study were obtained through pretest, post-test questions contained in the Quizizz Game application from observations and documentation. The instruments used to collect data are questionnaires and tests. The technique used to analyze the data is descriptive qualitative and quantitative analysis. The results of the study were that students obtained a percentage of learning completeness of 43.47%. After being given action I, the average score was 72, with a learning completeness percentage of 60.86% in Cycle I. In Cycle II, the average score increased to 85 with a learning completeness percentage of 95.65%. From the analysis above, it can be concluded that the application of the Quizizz Game learning media can increase students' interest and learning achievement. This research implies that teachers can use the application of the Quizizz Game learning media to increase student interest and learning outcomes.